Searching for the secret to sovereignty in the canterbury tales - Azyyati Alias (2013)
This essay will seek to study the notion of sovereignty in The Canterbury Tales; specifically in these tales: “The Wife of Bath Prologue & Tale”, “The Franklin’s Tale” and “The Clerk’s Tale”. In addition this essay will attempt to explore the definition of sovereignty, its workings as well as its overall effect on understanding the link between the tales in The Canterbury Tales. In my opinion, Chaucer had a consistent message of sovereignty between these three tales as well as in “The General Prologue”. Sovereignty is inevitable within society and what is more important is how we seek to achieve it.